Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Answer:
Step-by-step explanation:
x = -5/8 and y = -7/4
so
x = -0.625 and y = -2.25
Answer:
x = -0.625
y = - 1.75
Step-by-step explanation:
y = 2x - 1/2 ------------(I)
2x - 3y = 4 ---------(II)
Substitute y =2x - 1/2 in (II)
[tex]2x - 3*(2x - \dfrac{1}{2})=4\\\\\\2x - 6x + \dfrac{3}{2}=4\\\\-4x = 4-\dfrac{3}{2} = \dfrac{8}{4}- \dfrac{3}{2}\\\\-4x = \dfrac{5}{2}\\\\x = \dfrac{5}{2}* \dfrac{1}{-4}\\\\x= \dfrac{-5}{8}\\\\x= -0.625[/tex]
Plugin x = -0.625 in equation (I)
[tex]y = 2*(-0.625) - 0.5\\\\y = -1.25 - 0.5\\\\y = -1.75[/tex]
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.